Nitric Oxide (NO) as Antioxidant Protects HT22 Cells and Biomolecules against Fenton's Reagent‐Induced Damages via Multiple Pathways. Issue 3 (22nd March 2016) - Li, Xican; Lin, Jing; Gao, Yaoxiang; Tian, Ruimin; Chen, Dongfeng
Abstract: The role and mechanisms of the interaction of NO with OH radical remain controversial. To some extent, this is because previous studies have inappropriately used NO donors in place of aqueous NO. The present study thereby uses aqueous solutions of NO to explore the interaction of NO with Fenton's reagent. In the study, NO effectively reduced Fenton's reagent induced damage to hippocampal neuronal cells (HT22 cells), as well as to various biomolecules including DNA, Adenine, Uracil, Thymine, Cytosine, Guanine, pepsin (protein), and linoleic acid (lipid). Ion chromatography analysis suggests the generation of NO3 − and NO2 − ; while HPLC‐ESI‐MS revealed that NO could link to the O atom of a galvinoxyl via a σ‐bond. NO was also found to bind to Fe 2+ and reduce Fe 3+ →Fe 2+ . These findings indicate that, ( i ) NO can effectively protect against cellular and biomolecular damage induced by Fenton's reagent, possibly via multiple pathways, including binding to Fe 2+, destroying [FeO] 2+ to block the OH generation, combining with H2 O2, bonding with OH; ( ii ) Fe 3+ ‐reducing provides a recycle of Fe 2+ source; ( iii )In the interaction with Fenton's reagent, NO plays an antioxidant role and yields NO3 − and NO2 − . Abstract : NO can effectively protect HT22 cells and biomolecules against Fenton's reagent‐induced damages via multiple pathways, including binding to Fe 2+, destroying [FeO] 2+ to block the OH generation, combining with H2 O2, bonding with OH. Meanwhile, Fe 3+ ‐reducing by NO provides a recycle of Fe 2+ source. In a word, NO plays an antioxidant role in the interaction with Fenton's reagent, to yield the final products NO3 − and NO2 – .